أثر سياسة السجلات المحاسبية المفتوحة كأحد آليات إدارة التكلفة في تحقيق الميزة التنافسية للشركات الصناعية المساهمة العامة الأردنية (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The aim of this research is to study and test the impact of the policy of open-book accounting as one of the cost management mechanisms in achieving the competitive advantage in Jordanian industrial public companies, to achieve the objectives of the study, a field study was conducted by surveying the views of a sample of the accountants of the Jordanian industrial public companies. Hence the arithmetical Means, the Standard Deviations, the Significant Value and the Simple Linear Regression are used to test the research hypotheses and to achieve the research goals. The results of the study showed that there is a statistically significant effect of the policy of open-book accounting as one of the cost management mechanisms in achieving the competitive advantage of Jordanian industrial public companies. The study also showed a statistically significant effect of the policy of open-book accounting in achieving competitive advantage through the dimensions of the advantage (Cost, quality, flexibility, delivery) to the Jordanian industrial public companies.